Relevance of donor-specific antibody monitoring after kidney transplantation: findings from the Collaborative Transplant Study and the Heidelberg Transplant Center - Süsal, Caner; Aykut, Güçlü; Morath, Christian; Fichtner, Alexander; Unterrainer, Christian; Scherer, Sabine; Tran, Thuong Hien; Mehrabi, Arianeb; Zeier, Martin; Tönshoff, Burkhard (HLA, 2019)
Monitoring of donor-specific HLA antibodies (DSA) has become part of the clinical routine in kidney transplantation. This paper gives a brief overview on data from the Collaborative Transplant Study (CTS) and the Heidelberg Transplant Center on the clinical relevance of post-transplant DSA monitoring in patients undergoing renal transplantation. The obtained findings underline the importance of DSA monitoring in the post-operative course in immunologically high-risk patients and patients with deterioration of graft function. Especially in patients with a pre-activated immune system, a gap in the immunosuppressive therapy appear to lead to persistence, reappearance or de novo occurrence of strong, complement-activating DSA, resulting in severe antibody-mediated rejection (AMR) and, without timely intervention, in AMR-related graft loss.